Power Quality Improvement with Three-Phase Shunt Active Power Filter Prototype Based on Harmonic Component Separation Method with Low-Pass Filter - Marian Gaiceanu; Silviu Epure; Razvan Constantin Solea; Razvan Buhosu (Energies, 2025)
This work contributes to both Romania’s and the European Union’s energy policies by highlighting the research results obtained within the Dunarea de Jos University of Galati, but also through the technological transfer of this knowledge to the industry. In order to improve the power quality of the nonlinear loads connected to the electrical grid, a three-phase shunt active power filter prototype based on the Harmonic Component Separation Method with a Low-Pass Filter was used. The active power filter is connected at the Point of Common Coupling to compensate for individual loads or even all of them simultaneously. Therefore, active power filters can be used to compensate for the power factor and reduce the harmonic distortion of power supplies, or for processes subsequently connected to additional nonlinear loads, thus improving the energy efficiency. The shunt active power filter prototype is composed of the power side (three-phase insulated gate bipolar transistor bridge, DC link capacitor precharge system, inductive filter) and the control side (gate drive circuits, control subsystems, signal acquisition system). The filter control strategy is based on the principle of separating harmonic components with a low-pass filter, implemented by the authors on the industrial prototype. In this paper, the main technical features of the industrial shunt active power filter prototype are specified. The authors of this paper involved three cascaded control loops: the DC link voltage control loop, the shunt active power filter current control loop and the phase-locked loop. Both simulation and experimental results for the shunt-type active power filter prototype were obtained. By analyzing the obtained waveforms of the power supply source in two cases (with and without an active power filter), a decrease in the total harmonic distortion was demonstrated, both the voltage harmonic distortion factor THDu and the current harmonic distortion factor THDi in the case of the active power filter connection. By using the Field-Programmed Gate Array processing platform, the powerful computational speed features were exploited to implement the active shunt power filter control on an experimental test bench. Conducting source current harmonics mitigation increased the efficiency of the power system by decreasing the respective harmonic Joule losses. The energy-saving feature led to the increased added value of the parallel active power filter. Through the performed laboratory tests, the authors demonstrated the feasibility of the proposed control solution for the industrial prototype. In accordance with the European Union’s Research and Technological Development Policy, the development of an innovation ecosystem was taken into consideration. The unified and efficient integration of all the specific actors (enterprises, research institutes, universities and entrepreneurs) in innovation was achieved.